Mechanical system design - Siddiqui, K. U. (New Age International, 2007)
To be able to evolve such products and work in multidisciplinary teams, a very clear understanding of flow of material, energy and information is needed; points of observation and places of interfaces to outside systems need to be specified. As compared to well-established products, these new products require to be evolved from the concept to function to design to prototyping and testing stages. Due to increasing short life of product designs, these processes have to be carried out in ever decreasing time spans. This can be achieved often by resorting to model-based computer simulation, virtual prototyping and rapid prototyping techniques. Computer simulation requires mathematical model of the system to be built with all the interacting components and it leads to design development and optimization; virtual prototyping helps in designing real world interfaces and spatial description. Rapid prototyping helps in actual testing of the product. A systems-based approach to mechanical design helps in carrying out all these activities. Finally, an application of 'A Case Study' method is followed. -- Book Description.